PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VA SDN 29 PEKANBARU - Nurasya Nurasya; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the low learning outcomes of fifth grade students of SDN 29 Pekanbaru, KKM assigned in school that is 75. From 38 students, who reached the KKM is just 15 students (39,47%), whereas students who have not yet reached the KKM is 23 students (60.52%) with an average rating of class 60,92. The purpose of this research is to improve the learning results of social sciences (IPS) of fifth grade students of SDN 29 Pekanbaru with the application of the think talk write learning model. The research results obtained average value score increased 60.92 from basic cycle I was 18.56% become 72.23. In cycle II, the average value of the students also experienced an increase from 33.47% become 81.31. On a base score of classical succes learning of student was 39.47% (not succes). After applied think talk write learning model on cycle I classical succes learning of students increased to 65.78% (not succes), in cycle II classical succes learning of students rose to 86.84% (succes). The activity of the teacher in the first meeting of the cycle I is 66.66% by category is enough. The second meeting rose to 77.77% with categories of good. At the first meeting of the cycle II teacher activity rose to 86.11% by very good category. At the second meeting increased to 91.66% by very good category. The activity of the students at the first meeting of the cycle I got was 63.88% by enough category. The second meeting rose to 77.77% with good categories. At the first meeting of the cycle II activity of students increased to 80.55% with good categories. At the second meeting rose to 88.88% by very good category.Keywords: Think talk write, The results of IPS study